Diseño de la cadena de abastecimiento para concentrados avícolas en Agrofinca del llano (Castilla la Nueva) - Fajardo Luque, Lina Rocío; Hernández Quiroz, Brayan Esteban (Universidad Antonio Nariño, 2021)
The purpose of this research is to design the supply chain for poultry concentrates in the Agrofinca del llano company located in Castilla la Nueva to improve the level of service in the company since it currently has a stock break, delays in the launch of purchase orders, lack of stock control in warehouse and empirically estimating the size of the order lots. In the first instance, the diagnosis, measurement of key logistics performance indicators and process survey were carried out. The second stage includes the systematization and analysis of the historical sales of 2019 and 2020, as well as the projection of demand for the year 2021 through the selection of the forecasting method that best adapts to the behavior patterns in sales. The parameters for the inventory management model were established based on the optimization of supply and storage costs, as well as the optimal number of orders and the reorder point that allows the company to satisfy the estimated demand. Subsequently, the supply policy was established to guarantee efficiency in the processes established from the issuance of the purchase to the storage of the concentrates